Julien Green and the Art of Biographical Writing - Michael O’Dwyer (Pitannâ Lìteraturoznavstva)
Contemporary critics agree that biographical writing belongs as much to the domain of Literature as it does to History. Mauriac saw parallels between biographical writing and the novel form. Daniel Madelénat also emphasises the literary dimension of biography. Writing a biography is also seen as a form of catharsis for the writer as he faces his own deep preoccupations. Critics agree that a biography tells us as much about the writer as it does about the subject.Chateaubriand stated that the biographer is analysing his own soul while attributing it to another person. Jean Lacouture states that in a biography we are dealing with a portrait of the model and not of the artist. Madeleine Lazard adds that, in a biography, the subject is a reflection of the temperament of the writer. In our study of Julien Green’s biography of Saint Francis of Assisi and of his biographical essay on Hawthorne, we will see that the author reveals the principal preoccupations which form the basis of his fictional world. We will see that, for Green, biographical writing is a mirror and that the author presents us with a literary transformation of the image which he finds in the mirror.